2011
DOI: 10.1016/j.ajpath.2011.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Molecular Events in Thyroid Neoplasia Provides Evidence for Distinct Evolution of Follicular Thyroid Adenoma and Carcinoma

Abstract: Benign hypofunctional cold thyroid nodules (CTNs) are a frequent scintiscan finding and need to be distinguished from thyroid carcinomas. The origin of CTNs with follicular morphologic features is unresolved. The DNA damage response might act as a physiologic barrier, inhibiting the progression of preneoplastic lesions to neoplasia. We investigated the following in hypofunctional follicular adenoma (FA) and follicular thyroid cancer (FTC): i) the mutation rate of frequently activated oncogenes, ii) the activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
(59 reference statements)
0
10
0
2
Order By: Relevance
“…A recent study suggested that the nuclear peroxisome proliferator-activated receptor γ (PPARγ) could activate CHK2 in the development of follicular thyroid cancer [24]. In addition, PPARγ transcription has been shown to be regulated by STAT-5 in adipogenesis [25].…”
Section: Resultsmentioning
confidence: 99%
“…A recent study suggested that the nuclear peroxisome proliferator-activated receptor γ (PPARγ) could activate CHK2 in the development of follicular thyroid cancer [24]. In addition, PPARγ transcription has been shown to be regulated by STAT-5 in adipogenesis [25].…”
Section: Resultsmentioning
confidence: 99%
“…Western Blot analysis was performed on samples of inguinal WAT (iWAT), gonadal WAT (gWAT) and BAT as described previously45. The following antibodies and dilutions were used: mouse polyclonal anti-Ucp1 antibody (1:500; Merck Millipore; Darmstadt, Germany), pHSL and HSL(1:1000; Cell Signaling Technology, Danvers, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Moleculargenetic analyses indicate that specific genetic changes are associated with both subtypes of differentiated thyroid cancer In cases of PTC, BRAF as well as modified RET/PTC and trc oncogenes could be verified, whereas in cases of FTC, PAX8/PPARγ rearrangements and RAS mutations could be found [14]. Whether FTC develops directly from follicular thyroid cells or from follicular adenomas is still a matter of scientific controversy [14,17]. In addition to the described mutations, epigenetic factors leading to gene activation or deactivation may play a role in the development of differentiated thyroid cancer and are co-determinants of the phenotypical appearance of PTC and FTC tumors [18].…”
mentioning
confidence: 99%